Remarks on the controllability of nonlinear perturbations of Volterra integrodifferential systems. (1995) - Balachandran, K.; Balasubramaniam, P.
Abstract : Sufficient conditions for the complete controllability of nonlinear perturbations of Volterra integrodifferential systems with implicit derivative are established. The results generalize the results of Dauer and Balachandran [9] and are obtained through the notions of condensing map and measure of noncompactness of a set.